Association of CACNA1C Variants with Bipolar Disorder in the Korean Population - Kim, Soojin (Psychiatry Investig, 2016)
OBJECTIVE: Previous studies have suggested an association between CACNA1C and susceptibility of bipolar disorder. In this study, we examined the association of CACNA1C variants with bipolar disorder in the Korean population. METHODS: We selected 2 CACNA1C single nucleotide polymorphisms (SNPs), namely, rs723672 and rs1051375, based on their functions and minor allele frequencies described in previous studies. Genotypes of these 2 SNPs were analyzed by extracting DNA from blood samples collected from 287 patients with bipolar disorder and 340 healthy controls. RESULTS: Genotype frequencies of both rs723672 and rs1051375 SNPs were significantly different in patients and controls (p=0.0462 and 1.732E-14, respectively). Dominant, recessive, and allele models showed significant differences between patients and controls with respect to the rs1051375 SNP (p=1.72E-11, 4.17E-10, 4.95E-16, respectively). CONCLUSION: Our results suggested that CACNA1C SNPs rs723672 and rs1051375 were associated with bipolar disorder in the Korean population. In addition, our results highlighted the importance of CACNA1C in determining susceptibility to bipolar disorder.